Pengaruh Corporate Social Responsibility (CSR) dan Struktur Modal terhadap Profitabilitas Bank Umum Syariah di Indonesia - Beby Arini Mardhatillah; Bambang Waluyo; Dede Abdul Fatah (LPMP Imperium, 2020)
Purpose- This study aims to analyze the influence of Corporate Social Responsibility (CSR) and Capital Structure on the Profitability of Islamic Commercial Banks in Indonesia for the 2011-2017 period. Methods- Research uses a quantitative approach. Samples were taken by purposive sampling technique, amounting to 5 Islamic commercial banks in Indonesia. Data analysis technique using multiple linear regression with the assistance of the EVIEWS 9 program. Finding- The research results prove that CSR has an effect, but not significantly, on profitability. DAR has a positive effect on profitability. CSR and DAR together have a positive effect on profitability. The implications and suggestions are described in the article AbstrakTujuan- Penelitian ini bertujuan untuk menganalisis pengaruh Corporate Social Responsibility (CSR) dan Struktur Modal terhadap Profitabilitas Bank Umum Syariah di Indonesia periode 2011-2017. Metode- Riset menggunakan pendekatan kuantitatif. Sampel diambil dengan teknik purposive sampling berjumlah 5 bank umum syariah di Indonesia. Teknik analisis data dengan regresi linier berganda berbantuan program EVIEWS 9. Temuan- Hasil riset membuktikan bahwa CSR berpengaruh namun tidak signifikan terhadap profitabilitas. DAR berpengaruh positif terhadap profitabilitas. CSR dan DAR secara bersama-sama berpengaruh positif terhadap profitabilitas. Implikasi dan saran dijelaskan dalam artikel.